Linking maternal psychopathology to children's excessive crying and sleeping problems in a large representative German sample—The mediating role of social isolation and bonding difficulties. (17th November 2022) - Lux, Ulrike; Müller, Mitho; Reck, Corinna; Liel, Christoph; Walper, Sabine
Abstract: Attaining self‐regulation is a major developmental task in infancy, in which many children show transient difficulties. Persistent, clinically relevant difficulties in self‐regulation include excessive crying or sleeping disorders. Many families with affected children are burdened with multiple psychosocial risk. This suggests that regulatory problems are best conceptualized as the maladaptive interplay of overly burdened parents and a dysfunctional parent–child interaction. The current study examines whether social isolation and bonding difficulties function as mediating mechanisms linking maternal psychopathology to (1) children's excessive crying and (2) sleeping problems. The sample comprised N  = 6598 mothers ( M  = 31.51 years) of children between zero to three years of age ( M  = 14.08 months, 50.1% girls). In addition to socio demographic data, the written questionnaire included information on maternal depression/anxiety, isolation, bonding, and children's regulatory problems. Hypotheses were tested with a mediation model controlling for psychosocial risk and child characteristics. As expected, maternal symptoms of depression/anxiety were linked to infants' excessive crying and sleeping problems. Social isolation and bonding difficulties mediated this association for excessive crying as well as for sleeping problems, but social isolation was a single mediator for sleeping problems only. The findings provide important insights in the mediating pathways linking maternal psychopathology to children's regulatory problems.